Properties of finger joint effect by diferrent types of adhesive and alignment / Muhammad Shahedie Mat Anuar - Mat Anuar, Muhammad Shahedie (2014)
This study was conducted to evaluate the properties of finger joint effect by diferrent types of adhesive and alignment. This three adhesive and the combination of same species were tested in horizontal and vertical orientation for bending properties (modulus of elasticity and modulus of rupture) conforming to the European standard (EN 408:2003). The result revealed that the speciment from the three adhesive and and different ways of alignment was strong enough to be use as material in funiture making. Thus, it can be concluded that finger joint Neolamarckia cadamba spp. Using three types of adhesive (Polyvinyl Acetate, Epoxy and Contact Adhesive) and different ways of alignment can successfully be produced as the main source of raw materials for finger joint.